Ni-supported palm oil fuel ash catalyst (Ni-POFA) from in situ glycine-nitrate combustion for methane cracking - N. H., E. Hanifa; Asmida, Ideris; M., Ismail (IOP Publishing, 2020)
Metal-supported catalysts synthesized using a conventional impregnation method are usually suffered from non-uniform distribution and agglomeration of catalyst particles. In this work, in situ glycine-nitrate combustion method has been explored to synthesize Ni catalyst supported on palm oil fuel ash (Ni–POFA). The properties and performance of the catalyst were compared with one produced using impregnation method. Effects of pretreatment and catalyst preparation method have been investigated and characterizations of POFA and Ni–POFA catalysts were performed using XRF, XRD, BET surface area, FESEM and TGA. Catalytic activity of the catalysts was evaluated for methane cracking at 550 °C. Results showed that pre-treatment has improved the composition of SiO2 in POFA from 42.4 to 72.0%. Ni–POFA catalyst synthesized using in situ glycine-nitrate combustion method exhibited a good catalytic performance during the methane cracking with an initial H2 yield of 6.4%. This was attributed to high Ni metal dispersion on POFA support. Nevertheless, the degradation of CH4 conversion for this particular catalyst was more significant than one produced using impregnation method. Catalyst prepared using in situ glycine-nitrate combustion was active towards carbon formation, thus led to an obvious formation of carbon on the catalyst surface. Additionally, catalyst preparation method influenced the type of carbon formed on the spent Ni–POFA catalysts.